Anti-Inflammatory Effects Of Mesenchymal Stem Cells Derived Extracellular Vesicle In Rat Model Of Chronic Obstructive Pulmonary Disease - Ridzuan, Noridzzaida (2022)
This study aimed to assess the anti-inflammatory effects of human umbilical cord mesenchymal stem cell (hUC-MSC) derived EV in a rat model of COPD. Human UC-MSC-EV were isolated and characterized by using transmission electron microscope, western blot, and nanoparticle tracking analysis